Lithium iron phosphate positive electrode material, preparation method thereof, positive electrode sheet, lithium ion battery, battery module, battery pack and power-consuming device
Through wet coating and two-stage sintering technology, oxides are used as the coating layer to solve the alkalinity problem of lithium iron phosphate positive electrode material on the surface, improve its processing performance and battery performance, and achieve higher energy density and circulation performance.
Patent Information
- Application Number
- CN202210299303.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-03-25
AI Technical Summary
During the preparation process, the residual lithium source of lithium iron phosphate positive electrode material causes the surface of the material to be alkaline, increase moisture absorption and impurity water, thereby reducing the battery life, and inducing the binder elimination reaction during the slurry adjustment process, resulting in chemical coagulation. glue.
Using wet coating and two-stage sintering, boron oxide, silicon oxide or aluminum oxide is used as the precursor of the coating layer, uniformly dispersed on the surface of the lithium iron phosphate matrix, lowering the pH of the material surface, and passing through the coating layer The precursor acts as a flux to promote crystal growth and improve compaction density.
It effectively reduces the surface pH of lithium iron phosphate positive electrode material, improves its processing performance and stability, reduces moisture absorption and chemical gel risks, thereby improving the energy density and circulation performance of lithium-ion batteries.
Smart Images

Figure CN115832236B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium battery materials, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, as well as a positive electrode sheet, a lithium-ion battery, a battery module, a battery pack and an electrical device comprising the lithium iron phosphate positive electrode material. Background Art
[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.
[0003] As a positive electrode material for lithium-ion batteries, lithium iron phosphate has high theoretical capacity, stable charge and discharge voltage, and a wide range of sources, and is suitable for large-scale application. However, the residual lithium source, such as LiOH, Li2CO3 or LiHCO3, in the preparation process of lithium iron phosphate materials will make the surface of the material alkaline (pH is about 9-10), which will make lithium iron phosphate more hygroscopic, and the water content of the prepared pole piece is difficult to control. The impurity water that is difficult to dry and remove will accelerate the occurrence of side reactions during the use of the battery, greatly reducing the battery life. In addition, during the slurry adjustment process of the positive electrode, the residual alkali on the surface of the lithium iron phosphate material will induce the elimination reaction of the binder, and then cross-link between molecules, resulting in an increase in the viscosity of the positive electrode slurry and even chemical gelation. Therefore, it is necessary to adopt certain strategies to reduce the alkalinity of the surface of the lithium iron phosphate material, improve its processing performance and material stability, and thus improve the performance of lithium iron phosphate system lithium-ion batteries. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a lithium iron phosphate positive electrode material with reduced surface pH and increased compaction density, so as to improve the energy density and battery cycle performance compared with the existing lithium iron phosphate positive electrode materials, and to provide a preparation method of the lithium iron phosphate positive electrode material, as well as a positive electrode sheet, lithium-ion battery, battery module, battery pack and electrical device containing the lithium iron phosphate positive electrode material of the present application.
[0005] In order to achieve the above-mentioned purpose, the first aspect of the present application provides a lithium iron phosphate positive electrode material, including a lithium iron phosphate matrix and a coating layer, wherein the coating layer is selected from one of boron oxide, silicon oxide and aluminum oxide, and the mass ratio of the coating layer to the lithium iron phosphate matrix is 0.01-1.18:100, preferably 0.05-0.87:100.
[0006] Therefore, the coating layer in the lithium iron phosphate positive electrode material of the present application can combine with the residual alkali on the surface of the lithium iron phosphate matrix, reduce the pH of the material surface, thereby improving the processing performance of the lithium iron phosphate positive electrode material, reducing the moisture absorption of the material, reducing the risk of chemical gelation of the slurry, and improving the stability and dispersibility of the slurry, so that the lithium-ion battery prepared therefrom obtains significantly improved cycle performance.
[0007] In any embodiment, the median particle size of the lithium iron phosphate positive electrode material is 2.1-2.5 μm.
[0008] Therefore, the lithium iron phosphate positive electrode material of the present application has a larger median particle size, which increases the compaction density of the lithium iron phosphate positive electrode material and obtains an improved gram capacity, thereby improving the energy density of the lithium ion battery prepared therefrom.
[0009] A second aspect of the present application provides a method for preparing a lithium iron phosphate positive electrode material, the method comprising the following steps:
[0010] (S1) dispersing a precursor of the coating layer in water, then adding iron phosphate, a lithium source, a carbon source and an appropriate amount of water, continuing to disperse, and drying to obtain a uniformly mixed powder, wherein the precursor of the coating layer is selected from one of tetramethylammonium silicate, boric acid, and aluminum chloride, and the mass ratio of the precursor of the coating layer to the iron phosphate is 0.02-1.2:100, preferably 0.1-0.9:100;
[0011] (S2) sintering the uniformly mixed powder obtained in step (S1) in two stages to obtain a lithium iron phosphate positive electrode material:
[0012] (S2-A) In an inert atmosphere, the temperature is increased at a rate of 1-5°C / min, and sintered at 180-250°C for 1-5h;
[0013] (S2-B) Sintering at 650-750°C for 8-12h in an inert atmosphere.
[0014] In any embodiment, the preparation method further includes a step (S3), wherein the step (S3) is to crush the lithium iron phosphate positive electrode material obtained in the step (S2) by using a gas flow milling method.
[0015] Therefore, the lithium iron phosphate positive electrode material obtained by the preparation method of the present application has an improved surface pH and an increased compaction density, the processing performance of the lithium iron phosphate positive electrode material is improved, the moisture absorption of the material is reduced, the risk of gelation is not likely to occur during slurry adjustment, and the slurry stability and dispersibility are improved, so that the lithium-ion battery prepared therefrom is improved in terms of energy density and cycle performance.
[0016] In any embodiment, in the step (S2-A), the heating rate is 2-4°C / min, the sintering temperature is 200-230°C, and the sintering time is 2-4h.
[0017] Therefore, by controlling the heating rate, sintering temperature and sintering time in step (S2-A), a uniform and dense coating layer can be formed on the surface of the lithium iron phosphate matrix, so that the obtained lithium iron phosphate positive electrode material has high consistency, improved surface pH and increased compaction density, so that the lithium ion battery prepared therefrom has improved energy density and / or cycle performance.
[0018] In any embodiment, in the step (S2-B), the temperature is increased at a rate of 5-8°C / min. Thus, the energy density and / or cycle performance of the lithium-ion battery can be improved.
[0019] In any embodiment, the inert atmosphere is argon or nitrogen.
[0020] In any embodiment, in the step (S2-A), an inert atmosphere is purged at a flow rate of 1-4 mL / min. Thus, the energy density and / or cycle performance of the lithium-ion battery can be improved.
[0021] In any embodiment, in the step (S1), the precursor of the coating layer is dispersed in water in a frosted dispersion manner, and then the iron phosphate, lithium source, carbon source and appropriate amount of water are added to continue frosted dispersion. As a result, the precursor of the coating layer is uniformly dispersed and attached to the surface of the lithium source and the iron phosphate particles by chemical adsorption or physical adsorption, so that the lithium iron phosphate positive electrode material has a reduced surface pH and an increased compaction density, and the processing performance is improved, so that the lithium ion battery prepared therefrom has an improved energy density and cycle performance.
[0022] In any embodiment, in the step (S1), the drying is performed by centrifugal spraying, thereby obtaining a lithium iron phosphate positive electrode material with high consistency.
[0023] In any embodiment, the lithium source is one or more of lithium carbonate, lithium nitrate, lithium hydroxide, and lithium acetate.
[0024] In any embodiment, the carbon source is one or more of sucrose, glucose, starch, and polyethylene glycol.
[0025] Therefore, the performance of lithium iron phosphate positive electrode materials can be improved by selecting lithium sources and carbon sources.
[0026] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer includes the lithium iron phosphate positive electrode material of the first aspect of the present application or the lithium iron phosphate positive electrode material prepared according to the method of the second aspect of the present application, and the content of the lithium iron phosphate positive electrode material in the positive electrode film layer is more than 10 weight%, based on the total weight of the positive electrode film layer.
[0027] In any embodiment, the content of the lithium iron phosphate positive electrode material in the positive electrode film layer is 95-99.5% by weight, based on the total weight of the positive electrode film layer.
[0028] The fourth aspect of the present application provides a lithium ion battery, which includes the lithium iron phosphate positive electrode material of the first aspect of the present application or the lithium iron phosphate positive electrode material prepared according to the method of the second aspect of the present application or the positive electrode sheet of the third aspect of the present application. As a result, the lithium ion battery of the present application obtains significantly improved energy density and cycle performance.
[0029] A fifth aspect of the present application provides a battery module, which includes the lithium-ion battery of the fourth aspect of the present application.
[0030] A sixth aspect of the present application provides a battery pack, which includes the battery module of the fifth aspect of the present application.
[0031] The seventh aspect of the present application provides an electrical device comprising at least one selected from the lithium-ion battery of the fourth aspect of the present application, the battery module of the fifth aspect of the present application, or the battery pack of the sixth aspect of the present application.
[0032] The battery module, battery pack and electrical device of the present application include the lithium-ion battery provided by the present application, and therefore have at least the same advantages as the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material of Example 1 of the present application.
[0034] Figure 2 This is a scanning electron microscope image of the lithium iron phosphate positive electrode material of Comparative Example 1.
[0035] Figure 3 is a schematic diagram of a lithium-ion battery according to one embodiment of the present application.
[0036] Figure 4 yes Figure 1 An exploded view of a lithium-ion battery according to an embodiment of the present application is shown.
[0037] Figure 5 is a schematic diagram of a battery module according to an embodiment of the present application.
[0038] Figure 6 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0039] Figure 7 yes Figure 6 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0040] Figure 8 Schematic diagram of an electrical device using a lithium-ion battery as a power source according to an embodiment of the present application.
[0041] Description of reference numerals:
[0042] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 lithium-ion battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0043] Below, the lithium iron phosphate positive electrode material and its preparation method, positive electrode plate, lithium-ion battery, battery module, battery pack and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0044] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0045] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0047] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0048] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0049] During the preparation of lithium iron phosphate, residual lithium sources on the surface, such as LiOH, Li2CO3 or LiHCO3, will make the surface of the material alkaline. On the one hand, this phenomenon will make the powder more hygroscopic, worsen the side reactions caused by trace water impurities in the battery, and accelerate battery aging; on the other hand, the alkaline surface is prone to cause the cross-linking and breaking of binders such as polyvinylidene fluoride (PVDF), causing chemical gelation of the slurry, making the coating uniformity and consistency worse, and the adhesion of the active material on the collector surface decreases, thereby affecting the battery performance. At present, the main method for reducing the pH of lithium-ion battery positive electrode materials is the water washing method, that is, using a large amount of aqueous solution to wash the positive electrode material, dissolving the residual alkali on the surface of the material into the water, so as to reduce the amount of residual alkali on the surface of the material, and then reduce the pH. However, the general water washing method is not effective in removing residual alkali on the surface, and is not green and environmentally friendly.
[0050] After repeated studies, the inventors of the present application have obtained a lithium iron phosphate positive electrode material with improved surface pH and increased compaction density by adopting wet coating (the modified additive is fully dissolved and dispersed in a solvent, and after adding it to a substrate, during stirring, evaporation / drying or filter pressing, the additive undergoes a chemical reaction and precipitates on the surface of the substrate to form a coating) and two-stage sintering, thereby achieving improvements in energy density and cycle performance compared to lithium iron phosphate positive electrode materials obtained by existing methods. On the one hand, the precursor of the coating layer is added in the early wet mixing and sand grinding stage of the powder, so that the precursor of the coating layer is evenly dispersed on the surface of the lithium source and the iron phosphate particles. The coating layer obtained after two-stage sintering has higher density and consistency. The coating layer is a Lewis acidic oxide, which can combine with the residual alkali on the surface of lithium iron phosphate to reduce the pH of the surface of the lithium iron phosphate material, thereby reducing the moisture absorption of the material, reducing the risk of chemical gelation during slurry adjustment, and improving the dispersion and stability of the slurry; on the other hand, during the preparation process, the precursor of the coating layer can be used as a flux to promote the growth of lithium iron phosphate crystals, increase the average particle size of the lithium iron phosphate positive electrode material, and improve the compaction density. Therefore, the lithium iron phosphate positive electrode material of the present application has improved energy density and cycle performance.
[0051] Specifically, the first aspect of the present application provides a lithium iron phosphate positive electrode material, comprising a lithium iron phosphate matrix and a coating layer, wherein the coating layer is selected from one of boron oxide, silicon oxide and aluminum oxide, and the mass ratio of the coating layer to the lithium iron phosphate matrix is 0.01-1.18:100, preferably 0.05-0.87:100.
[0052] The present application achieves improved processing performance of the lithium iron phosphate positive electrode material, reduced hygroscopicity of the material, reduced the risk of chemical gelation of the slurry, improved slurry stability and dispersibility, and significantly improved ring performance of the lithium iron phosphate positive electrode material by combining the coating layer (Lewis-acidic oxide) in the lithium iron phosphate positive electrode material and reducing the pH of the material surface.
[0053] In some embodiments, the median particle size of the lithium iron phosphate positive electrode material is 2.1-2.5 μm.
[0054] The present application uses the precursor of the coating layer as a flux to promote the growth of lithium iron phosphate crystals, thereby increasing the average particle size of the lithium iron phosphate positive electrode material, improving the compaction density, and obtaining an improved gram capacity, thereby improving the energy density of the lithium-ion battery prepared therefrom.
[0055] A second aspect of the present application provides a method for preparing a lithium iron phosphate positive electrode material, the method comprising the following steps:
[0056] (S1) dispersing a precursor of the coating layer in water, then adding iron phosphate, a lithium source, a carbon source and an appropriate amount of water, continuing to disperse, and drying to obtain a uniformly mixed powder, wherein the precursor of the coating layer is selected from one of tetramethylammonium silicate, boric acid, and aluminum chloride, and the mass ratio of the precursor of the coating layer to the iron phosphate is 0.02-1.2:100, preferably 0.1-0.9:100;
[0057] (S2) sintering the uniformly mixed powder obtained in step (S1) in two stages to obtain a lithium iron phosphate positive electrode material:
[0058] (S2-A) In an inert atmosphere, the temperature is increased at a rate of 1-5°C / min, and sintered at 180-250°C for 1-5h;
[0059] (S2-B) Sintering at 650-750°C for 8-12h in an inert atmosphere.
[0060] In some embodiments, the preparation method further includes a step (S3), wherein the step (S3) is to crush the lithium iron phosphate positive electrode material obtained in the step (S2) by using a gas flow milling method.
[0061] The present application firstly disperses the precursor of the coating layer uniformly on the surface of the lithium source and iron phosphate particles by wet coating, and then performs two-stage sintering. The precursor of the coating layer can act as a flux to promote the melting of the iron phosphate particles during the sintering stage. Therefore, the present invention can not only obtain a coating layer with high density and consistency, but also the oxide-coated lithium iron phosphate positive electrode material has a larger particle size and a lower surface pH, thereby improving the energy density and cycle performance of the lithium-ion battery prepared therefrom.
[0062] In some embodiments, in the step (S2-A), the heating rate is 2-4°C / min, the sintering temperature is 200-230°C, and the sintering time is 2-4h. By controlling the heating rate and / or sintering temperature and / or sintering time in the step (S2-A), a uniform and dense coating layer can be formed on the surface of the lithium iron phosphate matrix, so that the obtained lithium iron phosphate positive electrode material has high consistency, improved surface pH and increased compaction density, so that the lithium ion battery prepared therefrom has improved energy density and / or cycle performance.
[0063] In some embodiments, in the step (S2-B), the temperature is increased at a rate of 5-8°C / min. By controlling the temperature increase rate in the step (S2-B), the energy density and / or cycle performance of the lithium-ion battery can be improved.
[0064] In some embodiments, the inert atmosphere is argon or nitrogen.
[0065] In some embodiments, in the step (S2-A), an inert atmosphere is purged at a flow rate of 1-4 mL / min. By controlling the flow rate of the inert atmosphere purging in the step (S2-A), a more uniform and dense coating layer can be formed on the surface of the lithium iron phosphate substrate, thereby improving the processing performance of the lithium iron phosphate positive electrode material.
[0066] In some embodiments, in the step (S1), the precursor of the coating layer is dispersed in water in a frosted dispersion manner, and the iron phosphate, lithium source, carbon source and appropriate amount of water are subsequently added to continue frosted dispersion. Thus, in step (S1), the powder is dispersed in a frosted dispersion manner, and the precursor of the coating layer is uniformly dispersed and attached to the surface of the lithium source and the iron phosphate particles by chemical adsorption or physical adsorption. On the one hand, this uniformly distributed coating layer precursor makes the coating layer obtained after sintering have higher density and consistency. On the other hand, it can act as a flux to promote the melting of iron phosphate particles during the sintering stage, thereby obtaining lithium iron phosphate particles with larger particle size, thereby finally obtaining a lithium iron phosphate positive electrode material with reduced surface pH and increased compaction density.
[0067] In some embodiments, in the step (S1), drying is performed by centrifugal spraying. The temperature and time of spray drying may be the conventional temperature and time for spray drying in the art. Thus, the precursor of the coating layer is uniformly dispersed and attached to the surface of the iron phosphate and lithium carbonate particles by chemical adsorption or physical adsorption. On the one hand, the coating layer obtained after sintering has higher density and consistency, so that the surface pH of the lithium iron phosphate positive electrode material is reduced; on the other hand, the uniformly distributed precursor of the coating layer can act as a flux to promote the melting of the iron phosphate particles during the sintering stage, thereby obtaining lithium iron phosphate particles with larger particle size and higher compaction density.
[0068] In some embodiments, the lithium source is one or more of lithium carbonate, lithium nitrate, lithium hydroxide, and lithium acetate.
[0069] In some embodiments, the carbon source is one or more of sucrose, glucose, starch, and polyethylene glycol.
[0070] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer includes the lithium iron phosphate positive electrode material of the first aspect of the present application or the lithium iron phosphate positive electrode material prepared according to the method of the second aspect of the present application, and the content of the lithium iron phosphate positive electrode material in the positive electrode film layer is more than 10 weight%, based on the total weight of the positive electrode film layer.
[0071] In some embodiments, the content of the lithium iron phosphate positive electrode material in the positive electrode film layer is 95-99.5% by weight, based on the total weight of the positive electrode film layer.
[0072] The fourth aspect of the present application provides a lithium-ion battery, which includes the lithium iron phosphate positive electrode material of the first aspect of the present application or the lithium iron phosphate positive electrode material prepared according to the method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.
[0073] Typically, a lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. In this application, the battery group margin is 90-93%.
[0074] In addition, the lithium-ion battery, battery module, battery pack, and electrical device of the present application are described below with reference to the drawings as appropriate.
[0075] [Positive electrode]
[0076] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0077] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0078] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, stainless steel, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0079] In some embodiments, in addition to the positive electrode active material of the first aspect of the present application, the positive electrode active material may adopt the positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.
[0080] In some embodiments, the positive electrode film layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0081] In some embodiments, the positive electrode film layer may further include a conductive agent, which may include, for example, at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0082] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0083] [Negative electrode]
[0084] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0085] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0086] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0087] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The negative electrode active material may have an average particle size (D 10), having an average particle size (D 50 ), and having an average particle size (D) of 26 μm to 40 μm, preferably 30 μm to 37 μm 90 ).
[0088] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0089] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0090] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0091] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0092] [Electrolytes]
[0093] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0094] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0095] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0096] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0097] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0098] [Isolation film]
[0099] In some embodiments, the lithium-ion battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0100] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0101] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0102] In some embodiments, the lithium-ion battery may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0103] In some embodiments, the outer packaging of the lithium ion battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.
[0104] The present application has no particular limitation on the shape of the lithium-ion battery, which may be cylindrical, square, or any other shape. Figure 3 A lithium-ion battery 5 having a square structure is used as an example.
[0105] In some embodiments, reference Figure 4, the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the lithium-ion battery 5 can be one or more, and those skilled in the art can choose according to specific actual needs.
[0106] In some embodiments, lithium-ion batteries can be assembled into a battery module. The number of lithium-ion batteries contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0107] Figure 5 4 is an example of a battery module. Figure 5 In the battery module 4, the plurality of lithium-ion batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of lithium-ion batteries 5 may be fixed by fasteners.
[0108] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of lithium-ion batteries 5 are received in the receiving space.
[0109] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0110] Figure 6 and Figure 7 1 is a battery pack 1 as an example. Figure 6 and Figure 7 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0111] In addition, the present application also provides an electrical device, which includes at least one of the lithium-ion battery, battery module, or battery pack provided in the present application. The lithium-ion battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0112] As the electrical device, a lithium-ion battery, a battery module or a battery pack can be selected according to its usage requirements.
[0113] Figure 8 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or a battery module can be used.
[0114] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0115] Example
[0116] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0117] Example 1
[0118] 1) Preparation of lithium iron phosphate positive electrode material
[0119] (S1) iron phosphate, lithium carbonate, glucose, and boric acid were weighed in a mass ratio of 100:25:11:0.4, and boric acid was first added to water, and sand-milled at 2000 r / min for 1 h using a 0.3 mm pick bead, and then iron phosphate, lithium carbonate, glucose, and an appropriate amount of water (slurry solid content of 42%) were added, and sand-milled at 2000 r / min for 16 h, and then dried by centrifugal spray drying to obtain a uniformly mixed light yellow powder (water content of 1.5%);
[0120] (S2) using a tubular furnace to perform two-stage sintering on the uniformly mixed powder obtained in (S1), (S2-A) firstly, under a nitrogen purge with a flow rate of 2 mL / min, the temperature was raised to 250°C at a heating rate of 2°C / min, and sintered at 250°C for 3 h, and then the purge was stopped, (S2-B) maintaining the nitrogen atmosphere, the temperature was raised to 700°C at a heating rate of 5°C / min, and sintered at this temperature for 10 h to obtain a lithium iron phosphate positive electrode material;
[0121] (S3) crushing the obtained lithium iron phosphate positive electrode material by using a gas flow crushing method.
[0122] Scanning electron microscope using Zeiss Sigma300 and Oxford Instruments X-max-50mm 2 The X-ray energy spectrometer was used to analyze the mass ratio of the coating layer to the lithium iron phosphate matrix in the lithium iron phosphate positive electrode material. The test results are shown in Table 1-2.
[0123] 2) Preparation of button cells
[0124] The lithium iron phosphate positive electrode material, polyvinylidene fluoride (PVDF), and Super-P prepared above were added to N-methylpyrrolidone solvent (NMP) at a weight ratio of 90:5:5, and stirred in a drying room to form a slurry. The slurry was coated on aluminum foil, dried, and cold pressed to form a positive electrode sheet. The coating amount was 0.3g / cm 2 , compacted density is 2.5g / cm 3 .
[0125] A lithium sheet was used as the negative electrode, and a solution of 1 mol / L LiPF6 in a volume ratio of 1:1:1 EC+DEC+DMC was used as the electrolyte. Together with the prepared positive electrode sheet, a CR3032 button cell (hereinafter referred to as "button cell") was assembled in a button cell box. The diameter*thickness of the button cell = 30.0 mm×3.2 mm.
[0126] 3) Preparation of full battery
[0127] The lithium iron phosphate positive electrode material prepared above was mixed with the conductive agent Super-P and the binder PVDF in NMP at a weight ratio of 92:2.5:5.5, and then coated on both sides of the aluminum foil, dried, and cold pressed to obtain a positive electrode sheet. The single-side coating amount is 0.4g / cm 2 , compacted density is 2.5g / cm 3 .
[0128] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were mixed evenly in deionized water at a weight ratio of 90:5:2:2:1, and then coated on both sides of the copper foil, dried, and cold pressed to obtain the negative electrode sheet. The single-sided coating amount is based on maintaining the negative electrode to positive electrode capacity ratio of 1.1.
[0129] Using PE porous polymer film as the isolation membrane, stack the positive electrode sheet, isolation membrane, and negative electrode sheet in order, so that the isolation membrane is in the middle of the positive and negative electrodes to play a role of isolation, and then wind up to obtain a bare battery cell. The bare battery cell is placed in an outer package, injected with the same electrolyte as in the above preparation of the buckle battery, and packaged to obtain a full battery (hereinafter also referred to as "full battery"). The length × width × height of the full battery = 148mm × 28.5mm × 97.5mm, and the battery group margin is 91.0%.
[0130] Example 2
[0131] The process is the same as that of Example 1 except that boric acid is replaced with tetramethylammonium silicate in “1) Preparation of lithium iron phosphate positive electrode material”.
[0132] Example 3
[0133] Except that in “1) Preparation of lithium iron phosphate positive electrode material”, boric acid is replaced with aluminum chloride, the rest is the same as Example 1.
[0134] Embodiment 4-9
[0135] Except that in “1) Preparation of lithium iron phosphate positive electrode material”, the mass proportions of boric acid as a coating layer precursor are changed to 0.02, 0.1, 0.5, 0.7, 0.9 and 1.2 respectively, the rest are the same as Example 1.
[0136] Examples 10-13
[0137] The process is the same as that of Example 1, except that in step (S2-A) the material is first sintered at 180°C, 200°C, 210°C, and 230°C for 3 h, respectively.
[0138] Examples 14-17
[0139] The process is the same as in Example 1 except that in “1) preparation of lithium iron phosphate positive electrode material”, the material is first sintered at 250° C. for 1 h, 2 h, 4 h, and 5 h respectively in step (S2-A).
[0140] Examples 18-21
[0141] The process is the same as in Example 1 except that in “1) Preparation of lithium iron phosphate positive electrode material”, the temperature is first raised to 250°C at heating rates of 1°C / min, 3°C / min, 4°C / min, and 5°C / min, respectively, in step (S2).
[0142] Comparative Example 1
[0143] Iron phosphate, lithium carbonate and glucose were weighed respectively in a mass ratio of 1:0.25:0.11, added into water, and sand milled at 2000 r / min for 16 h using a 0.3 mm pick bead (the slurry solid content was 42%), followed by drying by centrifugal spray drying to obtain a light yellow powder (water content was 1.5%). The powder was sintered in a tubular furnace, and heated to 700°C at a heating rate of 5°C / min in a nitrogen atmosphere. The powder was sintered at this temperature for 10 h to obtain a lithium iron phosphate positive electrode material, which was crushed by a gas flow milling method.
[0144] 2. Testing of related parameters
[0145] (1) Compaction density test
[0146] Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument. Apply a pressure of 5T, read the thickness of the powder under pressure on the device (the thickness after pressure relief), and calculate the compaction density through ρ=m / v.
[0147] See Table 1-2 for test results.
[0148] (2) Surface pH test
[0149] The lithium iron phosphate positive electrode active material and pure water are mixed into a solution at a fixed ratio of 1:9 and sealed on a magnetic stirrer for 30 minutes. After stirring, the conical flask is placed in a 25°C water bath thermostat and left to stand for 1.5 hours. The pH composite electrode is inserted into the solution to form an electrochemical primary cell, whose electromotive force is related to the pH of the solution. The electromotive force of the primary cell is measured and directly expressed as a pH value.
[0150] See Table 1-2 for test results.
[0151] (3) Median particle size D50 test
[0152] Take a clean beaker, add an appropriate amount of lithium iron phosphate positive electrode active material, add a surfactant dropwise, add an appropriate amount of pure water, and use ultrasound at 120W / 5min to ensure that the material powder is completely dispersed in the water. The solution is poured into the injection tower of the laser particle size analyzer (Malvern Company, model: Mastersizer3000) and then circulated to the test optical path system with the solution. The particles are irradiated by the laser beam, and the particle size distribution characteristics of the particles are obtained by receiving and measuring the energy distribution of the scattered light (shading degree: 8-12%).
[0153] See Table 1-2 for test results.
[0154] 3. Battery performance test
[0155] (1) Capacity test with power off
[0156] At 2.5-3.65V, charge the button battery at 0.1C to 3.65V, then charge at constant voltage at 3.65V to a current of 0.05C, let it stand for 5 minutes, and then discharge it at 0.1C to 2.5V. The ratio of the discharge capacity to the mass of the positive electrode active material at this time is the material gram capacity (mAh / g).
[0157] See Table 1-2 for test results.
[0158] (2) Full electrical cycle performance test
[0159] At 25°C, the lithium metal battery was charged to 3.65V at a constant current of 0.5C, then charged at a constant voltage of 3.65V until the current dropped to 0.05C, and then discharged to 2.5V at a constant current of 1C. The first cycle discharge capacity (C d1 ); Repeated charging and discharging until the 400th cycle, the discharge capacity of the lithium battery after 400 cycles is recorded as C d400 Capacity retention rate = discharge capacity after 400 cycles (C d400 ) / First week discharge capacity (C d1 ).
[0160] See Table 1-2 for test results.
[0161]
[0162]
[0163] It can be seen from the above results that compared with the lithium iron phosphate positive electrode material without a coating layer (Comparative Example 1), the lithium iron phosphate positive electrode material of the present application has a larger median particle size, an improved compaction density, and the pH of the material surface is effectively reduced. Although the internal resistance of the lithium iron phosphate positive electrode material of the present application has increased (relative to Comparative Example 1, the internal resistance increase ratio does not exceed 6%), this is within the acceptable range of the battery. Therefore, the lithium-ion battery prepared from the lithium iron phosphate positive electrode material of the present application has a larger gram capacity and an improved capacity retention rate.
[0164] Figure 1 The scanning electron microscope image of the lithium iron phosphate positive electrode material prepared in Example 1 of the present application is shown. Figure 2 The scanning electron microscope image of the lithium iron phosphate positive electrode material prepared in Comparative Example 1 is shown. It can be seen that the particle size of the lithium iron phosphate positive electrode material of the present application is larger and the particle size distribution is wider.
[0165] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A lithium iron phosphate positive electrode material, characterized in that: The invention comprises a lithium iron phosphate matrix and a coating layer, wherein the coating layer is selected from one of boron oxide, silicon oxide and aluminum oxide, the mass ratio of the coating layer to the lithium iron phosphate matrix is 0.01-1.18:100, and the median particle size of the lithium iron phosphate positive electrode material is 2.1-2.5 μm.
2. The lithium iron phosphate positive electrode material according to claim 1, characterized in that The mass ratio of the coating layer to the lithium iron phosphate matrix is 0.05-0.87:
100.
3. The lithium iron phosphate positive electrode material according to claim 1, characterized in that The surface pH value of the lithium iron phosphate positive electrode material is 8.16-8.
45.
4. The lithium iron phosphate positive electrode material according to claim 1, characterized in that The gram capacity of the lithium iron phosphate positive electrode material is 149-154 mAh / g.
5. The lithium iron phosphate positive electrode material according to claim 1, characterized in that The compaction density of the lithium iron phosphate positive electrode material at 5T is 2.592-2.684 g / cm 3 .
6. A method for preparing a lithium iron phosphate positive electrode material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (S1): dispersing a precursor of the coating layer in water, then adding iron phosphate, a lithium source, a carbon source and an appropriate amount of water, continuing to disperse, and drying to obtain a uniformly mixed powder, wherein the precursor of the coating layer is selected from one of tetramethylammonium silicate, boric acid, and aluminum chloride, and the mass ratio of the precursor of the coating layer to iron phosphate is 0.02-1.2:100; (S2): The uniformly mixed powder obtained in step (S1) is subjected to two-stage sintering to obtain a lithium iron phosphate positive electrode material: (S2-A): Under an inert atmosphere, the temperature is increased at a rate of 1-5°C / min and sintered at 180-250°C for 1-5h; (S2-B): Sintering at 650-750°C for 8-12h in an inert atmosphere.
7. The method according to claim 6, characterized in that The mass ratio of the precursor of the coating layer to iron phosphate is 0.1-0.9:
100.
8. The method according to claim 6, characterized in that The method further comprises a step (S3), wherein the step (S3) is to crush the lithium iron phosphate positive electrode material obtained in the step (S2) by using a gas flow crushing method.
9. The method according to any one of claims 6 to 8, characterized in that: In the step (S2-A), the heating rate is 2-4°C / min, the sintering temperature is 200-230°C, and the sintering time is 2-4h.
10. The method according to any one of claims 6 to 8, characterized in that: In the step (S2-B), the temperature is increased at a rate of 5-8°C / min.
11. The method according to any one of claims 6 to 8, characterized in that: The inert atmosphere is argon or nitrogen.
12. The method according to any one of claims 6 to 8, characterized in that: In the step (S2-A), an inert atmosphere is purged at a flow rate of 1-4 mL / min.
13. The method according to any one of claims 6 to 8, characterized in that: In the step (S1), the precursor of the coating layer is dispersed in water in a frosted dispersion manner, and then iron phosphate, lithium source, carbon source and appropriate amount of water are added to continue frosted dispersion.
14. The method according to any one of claims 6 to 8, characterized in that: In the step (S1), drying is performed by a centrifugal spray method.
15. The method according to any one of claims 6 to 8, characterized in that: The lithium source is one or more of lithium carbonate, lithium nitrate, lithium hydroxide and lithium acetate.
16. The method according to any one of claims 6 to 8, characterized in that: The carbon source is one or more of sucrose, glucose, starch and polyethylene glycol.
17. A positive electrode plate, comprising a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer comprising the lithium iron phosphate positive electrode material according to any one of claims 1 to 5 or the lithium iron phosphate positive electrode material prepared by the method according to any one of claims 6 to 16, and the content of the lithium iron phosphate positive electrode material in the positive electrode film layer is more than 10 weight%, based on the total weight of the positive electrode film layer.
18. The positive electrode sheet according to claim 17, characterized in that: The content of the lithium iron phosphate positive electrode material in the positive electrode film layer is 95-99.5% by weight, based on the total weight of the positive electrode film layer.
19. A lithium ion battery, characterized in that: The invention comprises the lithium iron phosphate positive electrode material according to any one of claims 1 to 5, or the lithium iron phosphate positive electrode material prepared by the method according to any one of claims 6 to 16, or the positive electrode sheet according to claim 17 or 18.
20. A battery module, characterized in that: Includes the lithium ion battery as claimed in claim 19.
21. A battery pack, characterized in that: Comprising the battery module as claimed in claim 20.
22. An electrical device, characterized in that: Includes at least one selected from the lithium-ion battery of claim 19, the battery module of claim 20, or the battery pack of claim 21.
Citation Information
Patent Citations
Lithium iron phosphate nanocomposite cathode material suitable for aqueous binder system and preparation method thereof
CN105762334A
Positive electrode active material and preparation method therefor, battery paste, positive electrode and lithium battery
CN106935850A